2014
DOI: 10.1002/jctb.4550
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation brines from Spanish style green table olives processing: treatment alternatives before recycling or recovery operations

Abstract: BACKGROUND Fermentation brine from Spanish style green table olives processing (FTOP) is characterized by very high conductivity (around 88 mS cm‐1), high values of suspended solids (near 1300 mg L‐1), chemical oxygen demand (around 17 900 mg L‐1) and total phenols (1000 mg L‐1). In this work, fermentation brines have been exhaustively characterized and pH adjustment–sedimentation, coagulation–flocculation–sedimentation and adsorption with activated carbon have been evaluated. RESULTS AND CONCLUSIONS The pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…For instance, Aldana and coworkers reported a 20% COD elimination rate and 50% turbidity removal using effluent from a black table olive processing plant [14]. Ferrer-Polonio et al found a negligible COD reduction after applying commercial coagulants to wastewater from the production of green table olives; however, these authors used very low doses of the coagulants-flocculants tested [15].…”
Section: Preliminary Coagulation-flocculation Stagementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Aldana and coworkers reported a 20% COD elimination rate and 50% turbidity removal using effluent from a black table olive processing plant [14]. Ferrer-Polonio et al found a negligible COD reduction after applying commercial coagulants to wastewater from the production of green table olives; however, these authors used very low doses of the coagulants-flocculants tested [15].…”
Section: Preliminary Coagulation-flocculation Stagementioning
confidence: 99%
“…Most of the works, however, are published on the effluents used in wastewater treatment from olive oil production [12], which have significantly different properties from the effluents generated in table olive production [15], including a higher organic load and much lower conductivity.…”
Section: Preliminary Coagulation-flocculation Stagementioning
confidence: 99%
“…A source of hypersaline streams can be the production of pickled fruits and vegetables. One of these generated effluents is the fermentation brine from table olive processing (FTOP), whose conductivity can reach 80 ms/cm and its chemical oxygen demand (COD) could be more than 15,000 mg/L [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biological treatment is very complicated since salinity reduces the cellular activity significantly [ 3 ]. In the case of FTOP, the biodegradation of the organic matter is even slower due to the presence of phenolic compounds (around 1000 mg tyrosol eq·L −1 ) [ 2 ]. In this way, the start-up and operation of biological reactors treating this brine is very complicated [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the acid pH, the fermentation brine wastewater is also characterized by a high salt concentration (conductivity from to 95 mS•cm -1 ) and high soluble chemical oxygen demand (COD), of 15000 to 30000 mgO 2 •L -1 . Part of this organic matter corresponds to the phenolic compounds (these concentration varying from 1000 to 2000 mg of tyrosol equivalents•L -1 ) (García-García et al, 2011) (Ferrer-Polonio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%